2016
DOI: 10.1016/j.cmet.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Protein Lipoylation and the 2-Oxoglutarate Dehydrogenase Complex Controls HIF1α Stability in Aerobic Conditions

Abstract: SummaryHypoxia-inducible transcription factors (HIFs) control adaptation to low oxygen environments by activating genes involved in metabolism, angiogenesis, and redox homeostasis. The finding that HIFs are also regulated by small molecule metabolites highlights the need to understand the complexity of their cellular regulation. Here we use a forward genetic screen in near-haploid human cells to identify genes that stabilize HIFs under aerobic conditions. We identify two mitochondrial genes, oxoglutarate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(198 citation statements)
references
References 31 publications
14
172
1
Order By: Relevance
“…For example, Koivunen et al showed that L‐2HG inhibits PHD activity, leading to an increase in HIF‐1α levels, whereas D‐2HG promotes PHD (Table ). Meanwhile, Burr et al reported similar, but controversial, findings showing that L‐2HG inhibits PHD, whereas D‐2HG has no effect (Table ). Regarding IDH3, we found that the aberrant activation of wild‐type IDH3 inactivated PHD activity by decreasing intracellular levels of 2‐OG, resulting in the stabilization of HIF‐1α (Table ).…”
Section: Genetic Mechanistic and Functional Alteration‐mediated Mecmentioning
confidence: 94%
“…For example, Koivunen et al showed that L‐2HG inhibits PHD activity, leading to an increase in HIF‐1α levels, whereas D‐2HG promotes PHD (Table ). Meanwhile, Burr et al reported similar, but controversial, findings showing that L‐2HG inhibits PHD, whereas D‐2HG has no effect (Table ). Regarding IDH3, we found that the aberrant activation of wild‐type IDH3 inactivated PHD activity by decreasing intracellular levels of 2‐OG, resulting in the stabilization of HIF‐1α (Table ).…”
Section: Genetic Mechanistic and Functional Alteration‐mediated Mecmentioning
confidence: 94%
“…Lentivirus was prepared by transfection using Mirus Trans‐IT ® ‐293 Transfection Reagent in HEK293ET cells as previously described . The viral supernatant was collected after 48 h and filtered (0.45‐μm filter), and cells were transduced by spin infection at 750 × g , 37°C for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic screen identified novel genes that led to normoxic HIF stabilization (Burr 2016). This screen identified mitochondrial oxoglutarate dehydrogenase (OGDH) and lipoic acid synthase (LIAS), which both, when mutated, lead to an accumulation of L-2-hydroxyglutarate (L-2-HG).…”
Section: Chronic Hypoxic Adaptation Through Hifmentioning
confidence: 99%
“…This screen identified mitochondrial oxoglutarate dehydrogenase (OGDH) and lipoic acid synthase (LIAS), which both, when mutated, lead to an accumulation of L-2-hydroxyglutarate (L-2-HG). Due to structural similarity to 2-oxoglutarate, L-2-HG is a competitive inhibitor of the 2-oxoglutarate dependent dioxygenase family of enzymes that include the PHDs (Burr 2016). This finding suggests that the TCA cycle dysfunction that leads to 2-HG metabolite accumulation is also a potential mediator of HIF activation in addition to ROS signaling pathways.…”
Section: Chronic Hypoxic Adaptation Through Hifmentioning
confidence: 99%